Pengembangan Nugget Ayam dengan Jamur Tiram dan Kulit Buah Naga Merah sebagai Pangan Cepat Saji yang Tinggi Serat (Lembaga Penerbitan Unversitas Esa Unggul, 2022)
Today people prefer to eat fast food which high of fat, sugar, natrium and low of Fiber. This will increasing risk of metabolic disorder. Nugget is a fast food containing high fat and low fiber. Addition of high fiber food expected to improve nutritional value of nugget. This study formulated nugget with oyster mushroom and red dragon fruit peel that are high in fiber. The objective of this tudy was to determine comparison of organoleptic attributes (color, aroma, texture and taste) and proximat analysis (water,ash,fat,protein,carbohydrate and fiber) among nugget formulation with of oyster mushroom and red dragon fruit peel added. This was a quantitative study with 4 formulation of oyster mushroom and red dragon fruit peel addition to nugget (F0=0:0; F1=40:50; F2=80:100; F3=120:150). Organoleptic test was performed by 30 panelist on 4 formulation and proximate analysis was performed on F0 and F3 compared to National Standart of Nugget. Friedman test was perform to investigate the different of panelist organoleptic attribute. Statistical test showed that there was no significant different in all organoleptic attribute among 4 nugget formulation. Proxymate analysis showed that F3 was the best formulation based on the national standart of nugget. This study showed that addition of oyster mushroom and red dragon fruit peel didnt affect panelist preference and improving nutrition content of product.